Synthesis, structure and photocatalytic properties of coordination polymers based on pyrazole carboxylic acid ligands. Issue 41 (1st October 2020) - Lin, Chen-Lan; Chen, Yan-Fei; Qiu, Li-Juan; Zhu, Binglong; Wang, Xin; Luo, Shi-Peng; Shi, Wenyan; Yang, Ting-Hai; Lei, Wu
Abstract : The photocatalytic activities of two novel different 2-D coordination polymers constructed from 5-hydroxy-1 H -pyrazole-3-carboxylic acid ligand have been explored. Abstract : Three new compounds, namely, [Mn(hpcH)(H2 O)2 ]·H2 O (1 ), [Cd(hpcH)(DMF)(H2 O)] (2 ), [Cu(hpcH2 )2 (H2 O)2 ] (3 ), (hpcH3 = 5-hydroxy-1 H -pyrazole-3-carboxylic acid) were solvothermally synthesized and characterized in detail. Compounds 1 and 2 are coordination polymers (CPs), exhibit two-dimensional (2D) layered structures and crystallize in monoclinic lattices with the C 2 / c and P 21 / c space groups, respectively. Compound 3 shows a 3D supramolecular structure constructed from six-coordinated mononuclear Cu 2+ through hydrogen bonds and π–π stacking interactions. The hpcH3 ligand behaved in different coordinated modes in the three compounds. It lost two protons in compounds 1 and 2 and one proton in compounds 3 . Furthermore, the photocatalytic degradation properties of compounds 1 and 2 were investigated. The results indicate that 1 and 2 show excellent photocatalytic activities for methylene blue (MB) under visible light. The photocatalytic degradation efficiency of 2 reached 96.7% in 90 minutes. The possible photocatalytic mechanisms displayed by CPs 1–2 for the photodegradation of MB have been addressed through the trapping experiment and theoretical calculations.